How Not to Use the Involuntary Bankruptcy Process - Michael A. Friedman Esq.; Allison R. Day (Washington University Journal of Law & Policy, 2017)
This Article evaluates the issues arising under 11 U.S.C. § 303, which governs involuntary bankruptcies. The Authors being by presenting an overview of commencing an involuntary bankruptcy case, as highlighted by the lengthy litigation inspired by Rosenberg v. DVI Receivable XVII, LLC and its dismissal. The Article concludes that the current state of § 303 can open additional litigation replete with costs, awards, fees, and other bad-faith damages, and creditors should exercise caution before pursuing involuntary bankruptcy, especially it it’s likely to fair for meeting the statutory requirements.
Keywords: Chapter 7 Bankruptcy; Bankruptcy Code; Involuntary Bankruptcy; Creditor’s Rights; Standing; Federal Rules of Civil Procedure; Attorney’s Fees; Bankruptcy Petition; Bankruptcy Litigation; Punitive Damages; Federal Rules of Bankruptcy Procedure